AKUNTABILITAS PENGELOLAAN LAPORAN KEUANGAN ORGANISASI KEMAHASISWAAN DI LINGKUNGAN UPN VETERAN JAKARTA - Wiendy Prameswary (2023)
This research is using qualitative study aimed to explore about the accountability of financial management from student organization of UPN Veteran Jakarta. Therefore, to fulfill the standards of good governance as a form of responsibility, student organizations has a responsibility to implementing the accountability principles, including management its financial reporting. The research approach used is a phenomenological approach to seek the meaning of organization activities based on an experience from the other people. The data collected using several methods: observation, in-depth interview with main informant, key informant and supporting informant, as well as document studies. The result from this study shows: (1) organization students of UPN Veteran Jakarta already has a good division of tasks regulated in their respective AD/ART, (2) responsibility reports between implementing and existing standard procedures had not been fully implemented properly, (3) the objectives of the program have been achieved, and the authenticity has been verified by the supervisor or internal controller responsible of the program, (4) reporting of organizational responsibility to the public with authenticity and timely manner, has not been fully implemented. Keywords: student organizations, accountability, financial management reports.